Analisis Ukuran Perusahaan dan Profitabilitas Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Yang Tergolong LQ45 di BEI Periode 2011-2014) - Angrita Denziana; Winda Monica (Universitas Bandar Lampung (UBL), 2016)
The study aims is to examine and analyze (1) the effect of firm size on firm value, (2) the effect on the profitability of the enterprise value of companies belonging LQ45 in BEI Period 2011-2014. This study population is a company belonging to LQ45 in the 2011-2014 period. The sampling technique used was purposive sampling in order to obtain a total sample of 17 companies. The data used in this study was obtained from the annual financial statements of each company belonging LQ45 published through the official website www.idx.co.id. Data analysis techniques in this study using SEM-based Partial Least Square (PLS). The results showed that (1) the variable firm size of the company and no significant positive effect on firm value, (2) variable profitability and significant positive effect on firm value.